2016
DOI: 10.1093/ajh/hpw074
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor Stimulation for Resistant Hypertension

Abstract: Hypertension (HTN) is a worldwide epidemic. When untreated, HTN places patients at an elevated risk for several health conditions, including cardiovascular disease and end-organ damage. This effect is particularly pronounced in a subset of patients who experience treatment-resistant HTN despite the utilization of conventional medication and lifestyle interventions. For these challenging patients, ongoing research efforts continue to explore and develop novel nonpharmacologic therapies for resistant HTN. One su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that patients with hypertension develop vascular injury in the early course of the disease. Furthermore, vascular endothelial cell injury and dysfunction are important signs of hypertension and may even occur prior to the onset of hypertension ( 36 ). miRNAs serve important roles in endothelial cell injury and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that patients with hypertension develop vascular injury in the early course of the disease. Furthermore, vascular endothelial cell injury and dysfunction are important signs of hypertension and may even occur prior to the onset of hypertension ( 36 ). miRNAs serve important roles in endothelial cell injury and dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Carotid baroreceptor stimulation has been shown to exert marked blood pressure lowering effects which are mediated by the sympathoinhibitory properties of the procedure capable to substantially reduce (average reduction 30%–40%) muscle sympathetic nerve traffic. 46 Of special interest is the observation that the procedure when employed in congestive heart failure, i.e., a clinical condition characterized by a massive sympathetic activation, 47 may trigger profound sympathoinhibitory effects with a significant improvement in the clinical severity of the disease, as assessed by the New York Heart Association (NYHA) functional class. 48 …”
Section: Sns Responses To Renal Denervation and Carotid Baroreceptor Stimulationmentioning
confidence: 99%
“…Even if there are not yet important studies and clear protocols, baroreflex activation therapy (BAT) could become a promising option [46] in the treatment of RH. Particularly interesting for CKD patients is that BAT was not only shown to decrease office BP values in small prospective trials on CKD non-dialysis and dialysis patients [47, 48], but also to have renoprotective effects by significantly reducing proteinuria and improving eGFR [47].…”
Section: Haemorrhagic Strokementioning
confidence: 99%